Silencing of RpATG6 impaired the yolk accumulation and the biogenesis of the yolk organelles in the insect vector R. prolixus. - Priscila H Vieira; Larissa Bomfim; Georgia C Atella; Hatisaburo Masuda; Isabela Ramos (Public Library of Science (PLoS), 2018)
In oviparous animals, the egg yolk is synthesized by the mother in a major metabolic challenge, where the different yolk components are secreted to the hemolymph and delivered to the oocytes mostly by endocytosis. The yolk macromolecules are then stored in a wide range of endocytic-originated vesicles which are collectively referred to as yolk organelles and occupy most of the mature oocytes cytoplasm. After fertilization, the contents of these organelles are degraded in a regulated manner to supply the embryo cells with fundamental molecules for de novo synthesis. Yolk accumulation and its regulated degradation are therefore crucial for successful development, however, most of the molecular mechanisms involved in the biogenesis, sorting and degradation of targeted yolk organelles are still poorly understood. ATG6 is part of two PI3P-kinase complexes that can regulate the recruitment of the endocytic or the autophagy machineries. Here, we investigate the role of RpATG6 in the endocytosis of the yolk macromolecules and in the biogenesis of the yolk organelles in the insect vector Rhodnius prolixus. We found that vitellogenic females express high levels of RpATG6 in the ovaries, when compared to the levels detected in the midgut and fat body. RNAi silencing of RpATG6 resulted in yolk proteins accumulated in the vitellogenic hemolymph, as a consequence of poor uptake by the oocytes. Accordingly, the silenced oocytes are unviable, white (contrasting to the control pink oocytes), smaller (62% of the control oocyte volume) and accumulate only 40% of the yolk proteins, 80% of the TAG and 50% of the polymer polyphosphate quantified in control oocytes. The cortex of silenced oocytes present atypical smaller vesicles indicating that the yolk organelles were not properly formed and/or sorted, which was supported by the lack of endocytic vesicles near the plasma membrane of silenced oocytes as seen by TEM. Altogether, we found that RpATG6 is central for the mechanisms of yolk accumulation, emerging as an important target for further investigations on oogenesis and, therefore, reproduction of this vector.